Adaptasi Gaya Kepemimpinan Situasional di Lingkungan Pendidikan Pesantren Modern - Maulana Panji Saputra; Novita Sulastri Ningsih; Dawia Nur Azizah; Tuah Nur (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to describe the adaptive leadership strategies implemented by the Mudir 'Am (general director) of Al Ma'tuq Islamic Boarding School in Sukabumi. A qualitative descriptive approach was applied, utilizing data collection techniques including observation, in-depth interviews, and document analysis. The informants consisted of the pesantren’s leadership team, teaching staff, and administrative personnel directly involved in management activities. Data analysis followed the stages of data collection, data reduction, data presentation, and conclusion drawing. The theoretical framework of this research is based on the situational leadership model proposed by Hersey and Blanchard (as cited in Pasolong, 2008), which classifies leadership styles into four primary indicators: instruction, consultation, participation, and delegation. The research findings reveal that the Mudir 'Am demonstrates the application of all four situational leadership indicators in a dynamic manner. Regarding instruction, the leader is able to deliver clear and firm directives to all elements of the pesantren. In the aspect of consultation, there is evidence of active two-way communication, where input and suggestions from teachers and staff are welcomed and considered. Participation is reflected in the collective involvement of stakeholders in strategic decision-making processes. However, in the delegation domain, the authority delegated by the Mudir 'Am remains limited and is only granted under certain circumstances, tailored to the principal roles and responsibilities of each division within the pesantren.